2019
DOI: 10.1186/s12890-019-0989-1
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of systemic sclerosis related pulmonary arterial hypertension in Australia

Abstract: BackgroundTo quantify the financial cost of pulmonary arterial hypertension (PAH) in systemic sclerosis (SSc).MethodsHealthcare use was captured through data linkage, wherein clinical data for SSc patients enrolled in the Australian Scleroderma Cohort Study were linked with hospital, emergency department (ED) and ambulatory care databases (MBS) for the period 2008–2015. PAH was diagnosed on right heart catheter according to international criteria. Determinants of healthcare cost were estimated using logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…33 Similarly, an Australian study using data from 2008 to 2015 found that healthcare costs were almost twice as high among patients with SSc and PAH compared to those without PAH. 34 Our findings using more recent US data confirm the higher healthcare costs associated with CTD + PAH compared to CTD (without PAH), but also suggest a marked increase in the costs of CTD + PAH and CTD in the US with average annual all-cause total healthcare costs of $202,248 and $53,711, which is much more than expected from inflation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…33 Similarly, an Australian study using data from 2008 to 2015 found that healthcare costs were almost twice as high among patients with SSc and PAH compared to those without PAH. 34 Our findings using more recent US data confirm the higher healthcare costs associated with CTD + PAH compared to CTD (without PAH), but also suggest a marked increase in the costs of CTD + PAH and CTD in the US with average annual all-cause total healthcare costs of $202,248 and $53,711, which is much more than expected from inflation.…”
Section: Discussionsupporting
confidence: 80%
“…In an earlier US study using data from 2003 to 2014, average annual all‐cause total healthcare costs in 2014 USD over the 5‐year follow‐up period postdiagnosis ranged from $44,454 to $63,320 among patients with SSc and PAH and from $18,513 to $23,269 among patients with SSc without PAH 33 . Similarly, an Australian study using data from 2008 to 2015 found that healthcare costs were almost twice as high among patients with SSc and PAH compared to those without PAH 34 . Our findings using more recent US data confirm the higher healthcare costs associated with CTD + PAH compared to CTD (without PAH), but also suggest a marked increase in the costs of CTD + PAH and CTD in the US with average annual all‐cause total healthcare costs of $202,248 and $53,711, which is much more than expected from inflation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with a prospective multicenter study using the Australian Scleroderma Cohort Study (ASCS) database with a sample size of 5,527 SSc patients between 2008-2015 demonstrating higher hospital charges for these individuals. 17 The median THC in SSc-PAH was also significantly higher in a retrospective U.S. study during a 5-year follow-up period with a total cohort of 1,957 SSc patients with lung involvement. 18 It is important to understand the economic impact of PAH on the healthcare system to accelerate our efforts on prompt and aggressive man-…”
Section: Discussionmentioning
confidence: 90%
“…As there is no cure for SSc and few effective disease‐modifying agents, SSc is linked to significant morbidity and mortality and reduced health‐related quality of life. Furthermore, SSc is associated with a large healthcare cost, with a high annual health service utilization cost per individual 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SSc is associated with a large healthcare cost, with a high annual health service utilization cost per individual. 13,14 The consequences of SSc on activities of daily living change with disease state and time. 2,15 Individual descriptions of living with the disease range from bothersome to impossible to live with.…”
Section: Introductionmentioning
confidence: 99%